Role of self-regulating mechanisms in the Philippine television broadcasting industry. - Maslog, Kristyn Kay F. (2008)
This study was conducted with the general objective of finding out how to improve the enforcement of self-regulating mechanisms in the Philippine television broadcasting industry, mainly focusing in the largest networks in the country ABS-CBN and GMA 7.